Energy poverty and energy efficiency in emerging economies. (24th August 2022) - Li, Rui; Xin, Ying; Sotnyk, Iryna; Kubatko, Oleksandr; Almashaqbeh, Ismail; Fedyna, Svitlana; Prokopenko, Olha
Energy poverty and low energy efficiency of households in emerging economies is a challenging sustainability issue. Using the general least squares technique for time series it is found that if households' expenditures for utilities grow by one percentage point, the poverty headcount ratio below national poverty lines increases by three percentage points in Ukraine during the period 1999-2018. With GDP per capita rising by 100 USD, there is a decrease in the headcount ratio below national poverty lines by six percentage points. That is, even a slight increase in household incomes has a significant effect on reducing energy poverty. The results suggest that if GDP per capita increases by 1000 USD, the energy efficiency of GDP improves by one USD per kg of oil equivalent. Therefore, increased population well-being is a factor of energy poverty reduction and energy efficiency improvements. The rise of utilities prices contributes to the profitability growth of energy-efficient measures and the increase in utilities expenditures.